Kontinuitas dan Perubahan dalam Sistem Pendidikan Pesantren Salaf Modern di Indonesia - Dewi Urifah Salsabila; Sahman Z; Mukhlishin Mukhlishin (Sulawesi Tenggara Educational Journal, 2025)
Pesantren as an indigenous Islamic educational institution continues to adapt in the midst of the dynamics of educational modernization, globalization, and socio-cultural development of the community. The renewal of salaf Islamic boarding schools towards a more modern education system has become an important discourse in the study of contemporary Islamic education. This article aims to critically examine the pattern of renewal of salaf pesantren by emphasizing aspects of continuity and changes in educational goals, institutional systems, curriculum, and pesantren learning methodologies. This research uses a literature review approach by examining various scientific literature, both books and reputable journal articles, which discuss the transformation of Islamic boarding schools in Indonesia in the last five to seven years, as well as relevant classical literature as a conceptual basis. Data analysis was carried out through thematic synthesis to identify general trends, differences in approaches, and factors that affect the success of pesantren reform. The results of the study show that pesantren renewal is not dichotomous between tradition and modernity, but takes place in an adaptive manner through the principle of preserving essential Islamic values and adopting contextual modern elements. The update is seen in the integration of formal and non-formal education systems, the development of an integrated curriculum, and the application of more participatory learning methods. A conceptual understanding of Islamic boarding school modernization is needed as a dynamic process rooted in tradition as well as responsive to the demands of the times